Debating in teaching and learning English : theory and practice for pedagogy and curriculum - Wilson, Ben (Independent researcher) (Bloomsbury Academic, 2024)
Debating is a well-known method of dialogic speaking and is widely practiced, intercontinentally and across diverse cultural boundaries, to develop interaction, negotiation, agreeing and disagreeing in TEFL. This book invites scholars and practitioners to reflect on the demands of the current age for moving forward educational practice. It examines how debating can promote a holistic understanding and improvement of experience of education, and indeed academic outcomes. The author details the experiences of an adult EFL debate group in a private language school in the North of Italy, reporting how the participants experience the pedagogy, so as to offer insights into it as a form of teaching speaking in adult EFL.